Degassing of FC-72 in Microgravity - Weiland, Danielle; Crosby, Kevin; Hall, Nancy (Proceedings of the Wisconsin Space Conference, 2014)
The Carthage College Microgravity Team designed and built a system to degas FC-72 during microgravity conditions through the NASA SEED program. FC-72 is an electronic coolant with low boiling point and surface tension that would be an ideal coolant for use in a two-phase cooling system onboard spacecraft [3M, 2013]. The goal of the project was to remove the dissolved gases from liquid FC- 72 to improve the efficiency of flow boiling in microgravity as part of the Flow Boiling and Condensation Experiment conducted jointly by NASA Glenn Research Center (GRC) and Purdue University. A radial membrane contactor was used to remove the gases from the liquid during microgravity. Data from the lab was compared with the parabolic flight data to determine the relative effectiveness of the radial membrane contactor in reduced gravity.Â